Influencers as a Means of Marketing Communications Strategy Digital Marketing Little PEP Jaya - Hasim Hasim; Dinna Nurdiani Hapsari (Journal Research of Social Science, Economics, and Management, 2021)
creative economic field production of clothing in the city is currently experiencing a significant increase, various Various methods and sales promotion strategies are carried out by them to introduce their products to the wider community through digital media including social media, Instagram, company web. Business competition is also very tight, this company tries to attract consumers to buy its products by carrying out promotional strategies through the role of an influencer, such as artists, fashion bloggers, fashion stylish, and others, in this way is expected to increase sales. This study aims to see an overview of digital marketing communication strategies through the role of an influencer applied by Little PEP Jaya. Based on the research theme, a suitable research method for digging up the data or information needed uses qualitative research methods with a descriptive approach. Data collection techniques in research are through semi-structured interviews conducted with informants who are closely related to the theme of this research, including influencers and management staff at Little PEP Jaya. research findings the researcher also conducted a literature study, either through communication books or through online sources relevant to this research. The results of this study are Little PEP Jaya's digital marketing communication strategy planning through influencers using Instagram social media as a medium for disseminating information. In planning the marketing communication strategy, Little PEP Jaya has communicators, namely influencers according to the character of the product, they have an age segmentation that is in accordance with the Little PEP Jaya brand image, namely children's and young parents' clothing, In the implementation of marketing communication strategies through influencers, Little PEP publicity Jaya asked for a message to be conveyed by communicators, namely influencers, those who designed it by adjusting the personality of the Influencers, but did not have a deadline.